Histologic Subtypes of Ovarian Carcinoma: Selected Diagnostic and Classification Problems in Bulgaria: Is Low Hospital Volume an Issue?. Issue 2 (March 2017) - Ivanova, Vesela; Dikov, Tihomir; Dimitrova, Nadya
Purpose: To provide an overview of the morphologic subtypes of ovarian carcinomas in Bulgaria in relation to current healthcare organization using Bulgarian National Cancer Registry data. Further, we investigated hospital volume as a factor influencing the quality of care for patients with ovarian cancer. Methods: Bulgarian National Cancer Registry ovarian carcinoma data were retrieved (2009-2011) and distribution of histologic types was analyzed. Cases were divided and compared with respect to main treatment: no surgery, surgery at hospitals dealing with ≥30 ovarian cancer patients/year (high volume), and surgery at hospitals dealing with <30 ovarian cancer patients/year (low volume). We then estimated the odds of being diagnosed with adenocarcinoma and carcinoma not otherwise specified (NOS) vs specified morphologies (serous, endometrioid, clear cell, and mucinous), including age, grade, stage, and hospital volume, in a logistic regression model. Results: A total of 2, 041 ovarian carcinomas were distributed as follows: serous 47.7%, mucinous 11.9%, endometrioid 5.8%, clear cell 1.8%, and adenocarcinoma and carcinoma NOS 32.5%. More than half of cancer patients (n = 1, 100, 53.9%) were surgically treated in low-volume hospitals and they had a larger proportion of cases with adenocarcinoma and carcinoma NOS: 33.3%, in comparison with 24.0% in high-volume hospitals (p<0.0001). The odds of being diagnosed with unspecified morphology, assumed as a proxy of suboptimal quality of care, are higher for patients surgically treated in low-volume hospitals (odds ratio 1.50 [95% confidence interval 1.21-1.87]) compared with high-volume hospitals after adjustment for age, stage, and grade. Conclusions: The results of our study may serve policymakers and healthcare professionals when optimizing diagnosis and treatment of ovarian cancer in Bulgaria.